2024
DOI: 10.1186/s12905-024-02965-9
|View full text |Cite
|
Sign up to set email alerts
|

Women’s autonomy and maternal health decision making in Kenya: implications for service delivery reform - a qualitative study

Easter Olwanda,
Kennedy Opondo,
Dorothy Oluoch
et al.

Abstract: Background Maternal and neonatal outcomes in, Kakamega County is characterized by a maternal mortality rate of 316 per 100,000 live births and a neonatal mortality rate of 19 per 1,000 live births. In 2018, approximately 70,000 births occurred in the county, with 35% at home, 28% in primary care facilities, and 37% in hospitals. A maternal and child health service delivery redesign (SDR) that aims to reorganize maternal and newborn health services is being implemented in Kakamega County in Keny… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Experiencing birthing trauma has shown to result in postpartum post-traumatic stress disorder (P-PTSD) and postpartum depression (PPD) [ 9 11 ]. Likewise, disempowering births can have long term impacts of maternal self-esteem [ 12 , 13 ]. Maternal mental health issues have resulted in numerous public health concerns, specifically regarding the decreased safety and negative health outcomes that the infant faces [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiencing birthing trauma has shown to result in postpartum post-traumatic stress disorder (P-PTSD) and postpartum depression (PPD) [ 9 11 ]. Likewise, disempowering births can have long term impacts of maternal self-esteem [ 12 , 13 ]. Maternal mental health issues have resulted in numerous public health concerns, specifically regarding the decreased safety and negative health outcomes that the infant faces [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ample daylight, thermal comfort, color, and noise control all contribute to environmental healing within a hospital [ 19 ]. Furthermore, patient health outcomes have been linked to the built environment of hospitals in multiple studies [ 13 , 20 , 21 ]. More specific to birthing, women have indicated that perceived hominess and control in the environment relate to their birthing experience [ 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%